The Emerging Role of Voltage-Gated Sodium Channels in Tumor Biology - Mao, Weijia; Zhang, Jie; Körner, Heinrich; Jiang, Yong; Ying, Songcheng (Frontiers in Oncology, 2019)
Voltage-gated sodium channels (VGSCs) are transmembrane proteins which function as gates that control the flux of ions across the cell membrane. They are key ion channels for action potentials in excitable tissues and have important physiological functions. Abnormal function of VGSCs will lead to dysfunction of the body and trigger a variety of diseases. Various studies have demonstrated the participation of VGSCs in the progression of different tumours, such as prostate cancer, cervical cancer, breast cancer and others, linking VGSC to the invasive capacity of tumour cells. However, it is still unclear whether the VGSC regulate the malignant biological behaviour of tumours. Therefore, this paper systematically addresses the latest research progress on VGSCs subunits and tumours and the underlying mechanisms, and it summarizes the potential of VGSCs subunits to serve as potential targets for tumour diagnosis and treatment.